Unexpected role of pig nostrils in the clonal and plasmidic dissemination of extended-spectrum beta-lactamase-producing Escherichia coli at farm level - Sandra Martínez-Álvarez; Pierre Châtre; Pauline François; Idris Nasir Abdullahi; Carmen Simón; Myriam Zarazaga; Jean-Yves Madec; Marisa Haenni; Carmen Torres (Ecotoxicology and Environmental Safety, 2024)
The presence of methicillin-resistant or -susceptible S. aureus in pig nostrils has been known for a long time, but the occurrence of extended-spectrum beta-lactamase (ESBL)-producing E. coli has hardly been investigated. Here, we collected 25 E. coli recovered from nasal samples of 40 pigs/10 farmers of four farms. Nine ESBL-producing isolates belonging to ST48, ST117, ST847, ST5440, ST14914 and ST10 were retrieved from seven pigs. All blaESBL genes (blaCTX-M-32, blaCTX-M-14, blaCTX-M-1, blaCTX-M-65, and blaSHV-12) were horizontally transferable by conjugation through plasmids belonging to IncI1 (n=3), IncX1 (n=3) and IncHI2 (n=1) types. IncI1-plasmids displayed different genetic environments: i) IS26-blaSHV-12-deoR-IS26, ii) wbuC-blaCTX-M-32-ISKpn26 (IS5), and iii) IS930-blaCTX-M-14-IS26. The IncHI2-plasmid contained the genetic environment IS903-blaCTX-M-65-fipA with multiple resistance genes associated either to: a) Tn21-like transposon harbouring genes conferring aminoglycosides/beta-lactams/chloramphenicol/macrolides resistance located on two atypical class 1 integrons with an embedded ΔTn5393; or b) Tn1721-derived transposon displaying an atypical class 1 integron harbouring aadA2-arr3-cmlA5-blaOXA-10-aadA24-dfrA14, preceding the genetic platform IS26-blaTEM-95-tet(A)-lysR-floR-virD2-ISVsa3-IS3075-IS26-qnrS1, as well as the tellurite resistance module. Other plasmids harbouring clinically relevant genes were detected, such as a ColE-type plasmid carrying the mcr-4.5 gene. Chromosomally encoded genes (fosA7) or integrons (intI1-dfrA1-aadA1-qacE-sul1/intI1-IS15-dfrA1-aadA2) were also identified. Finally, an IncY plasmid harbouring a class 2 integron (intI2-dfrA1-sat2-aadA1-qacL-IS406-sul3) was detected but not associated with a blaESBL gene. Our results evidence that pig nostrils might favour the spread of ESBL-E. coli and mcr-mediated colistin-resistance. Therefore, enhanced monitoring should be considered, especially in a sector where close contact between animals in intensive farming increases the risk of spreading antimicrobial resistance.